Evaluation of Deformation Behavior of Sand-Clay Mixture Under Traffic Loads - Fedakar, Halil I.; Cai, Wenjing; Rutherford, Cassandra J.; Cetin, Bora (Amer Soc Civil Engineers, 2020)
Vehicle traffic loading induces a heart-shaped stress path in deviatoric stress space [tau z theta to (sigma(z)-sigma(theta))/2], causing the rotation of principal stress direction acting on a soil element. A conventional triaxial test is not capable of applying the principal stress rotation induced by heart-shaped stress path and therefore, is not able to evaluate the behavior of soils accurately under traffic loads. However, a hollow cylinder test can simulate heart-shaped stress path imposed by traffic loading. In this study, the effect of heart-shaped stress path on the vertical deformation behavior of sand-clay mixture including 20% of clay by mass was experimentally investigated through hollow cylinder test. The tests in this study were conducted at three stages: i) saturation, ii) consolidation, and iii) shearing. The specimens were first saturated until Skempton's B >= 0.95 and then consolidated with K-0=0.5. Thereafter, the specimens were sheared under cyclic loadings involving vertical stress and shear stress. Experimental results indicate that the principal stress rotation induced by traffic loading significantly influences the permanent strain development in sand-clay mixture.
Cetin, Bora/0000-0003-0415-7139;